A Review on the Effect of Post-Weld Heat Treatment (PWHT) on its Thermal Analysis and Mechanical Properties of Welded Metallic Pipe - Roslan, Nurul Shahadah; Mohmad Hadzir, Muzzahir; Ismail, Iman Fitri; Mat, Mohamad Nur Hidayat; M. Yusup, Eliza (International Journal of Integrated Engineering, 2024)
Welding is a commonly used process in manufacturing and engineering, and it may create residual stress in the welded region that can cause problems during service. Thermal expansion of the post-weld heat treatment (PWHT) of steel carbon induces residual stress. To relieve the internal stresses in the weld zone, PWHT is used to soften the hardening zone, improve microstructures, and lower hydrogen content in the welded region. The pipe size, heating width, insulation conditions, heating rates, soaking temperature, and holding time are factors that influence PWHT procedures. This paper will explain clearly about the PWHT process and the effect of PWHT on the metallic metal.